(untitled) (Journal of Scientific Research, 2025)
It is very helpful to be able to predict different kinds of intermolecular interaction and the strength of the connection between the solute and solvent with thermo-acoustical and volumetric data. Protein and salts are two types of nutrients that are abundant in the human body. This study has examined a number of volumetric and thermo-acoustical properties of C6H9N3O2+H2O and C6H9N3O2+H2O+K2SO4 systems’ attributes. With ultrasonic velocities (U) and densities (ρ) of 0.02 – 0.2 mol-kg-1 concentration of protein (C6H9N3O2) in water and 0.1 mol-kg-1 concentration of aqueous potassium salt. The novelty of this tactic is that it exhibits biological and technical applications by observing the pattern of interaction between the protein and salt molecules, which will assist to build more effective future solutions.